Revitalisasi Ekonomi Kreatif di Indonesia melalui Penguatan Sektor Pariwisata: Revitalizing the Creative Economy in Indonesia through Strengthening the Tourism Sector - Maharani, Maharani; Laily Nisa, Fauzatul (JEMeS - Jurnal Ekonomi Manajemen dan Sosial, 2024)
The creative economy, as an approach to sustainable economic development, combines innovation with the use of renewable resources. It involves the integration of elements of knowledge innovation, creative technology, and culture. Indonesia's creative industry, which includes various sectors such as art, fashion and design, has a significant contribution to economic growth and job creation. The synergy between tourism and the creative industry, especially in the development of creative products and services, provides added value to tourist destinations and the local economy. However, to ensure sustainability, support from the government, private sector and active participation of local communities is needed.